An In vivo study: Adjuvant activity of poly-n-vinyl-2-pyrrolidone-co-acrylic acid on immune responses against Melanoma synthetic peptide. Issue 1 (1st January 2018) - Kızılbey, Kadriye; Mansuroğlu, Banu; Derman, Serap; Mustafaeva Akdeste, Zeynep
ABSTRACT: Peptides have been studied as an important class of components in medicine to control many major diseases with vaccination. Polymers as adjuvants are capable of enhancing the vaccine potential against various diseases by improving the delivery of antigens, and they reduce the booster doses of vaccines. In brief, polymers are promising candidates for peptide-based vaccine delivery platforms. The purpose of the present study was to create a possible alternative approach in the treatment of malignant melanoma and/or to prevent metastasis of melanoma. The study was designed as both an experimental and an in vivo study. We prepared a complex and covalent conjugate of MAGE-3 121–134 (L-L-K-Y-R-A-R-E-P-V-T-K-A-E) T-cell epitope as a vaccine candidate for melanoma. These conjugates were able to generate an immune response in mice after a single immunization, without the help of any external adjuvant. The peptide-polymer complexes activated the immune system in the best way and formed the highest antigen specific immune response. These results indicate the adjuvant activity of Poly(N-vinyl-2- pyrrolidone-co-acrylic acid) [P(VP-co-AA)] and the potential use of P(VP-coAA)-peptide based vaccine prototypes for future melanoma cancer vaccine formulations.